Co-differentiation and enrichment of corneal endothelial cells and keratocytes from human pluripotent stem cells - Abhinav Reddy Kethiri; Pyry Grönroos; Ajai Suwaraj Chinnaiah Nagaraj; Heli Skottman (Scientific Reports)
Abstract Corneal keratocytes (CK) and endothelial cells (CEnC) maintain corneal stromal transparency. Damage to these cell types can lead to visual impairment. Although corneal transplantation is effective, donor shortages limit its availability. Human pluripotent stem cells (hPSC) offer a promising alternative for generating corneal cell types. While hPSC-derived epithelial cells and CEnC are well-studied, attempts to differentiate CK from hPSC have received less attention. This study investigates the differentiation of hPSC-CK using defined culture conditions and approaches to enrich both CK and CEnC. hPSC were cultured on laminin 521 (LN-521) coatings and differentiated using transforming growth factor β (TGFβ) and glycogen synthase kinase-3 (GSK-3) inhibitors, along with retinoic acid (RA) with (mEn protocol) or without (En protocol) fibroblast growth factor-2 (FGF2). Differentiated cells were characterized using qPCR and immunofluorescence on days (D) 8, 10, and 13. CK enrichment utilized collagen-1-coated plates with keratocyte-specific media, while CEnC were purified through metabolic starvation. Results showed the formation of heterogenous cultures containing both CK and CEnC. CK-like cells expressed keratocan (KERA), lumican (LUM), paired box 6 (PAX6) and actin α2 (ACTA2) genes, with proteoglycan expression (lumican (LUM) and decorin (DCN)) increasing over time. En protocol however maintained a stable CK phenotype. Furthermore, enriched hPSC-CK were LUM+/DCN+/PAX6−/CD166− and hPSC-CEnC were CD166+/ZO-1+. Using xeno-free, defined conditions, we differentiated both CK and CEnC from hPSC using a single protocol with further optimized enrichment methods for hPSC-CK and hPSC-CEnC purification, advancing cell differentiation techniques.